Instituir en la Ley Orgánica de Régimen Tributario Interno (LORTI) un mecanismo para incluir al transporte público y taxis dentro de los regulados por el impuesto a la contaminación vehicular - Mina Márquez, Mirey Marlene (2015)
Once investigated the problem that causes the vehicular pollution, it mainly affects the health of the population and destroys the environment I have raised knowing the harm caused vehicular pollution both public transport and taxis since as stated the Organic Law Internal Tax Regime (Lortie) these are exempt from paying the tax on vehicle pollution and which studies are most pollution emanating from what I've seen necessary to find a mechanism to help resolve this serious drawback thereof having a importance social and legal. There is no doubt that human activity affects the natural environment causing serious consequences and effects in humans; mainly affecting the respiratory system of children and elderly by smog emanating from the buses that do not comply with the Road Transport Act and Road Traffic Safety which clearly defines to be performed continuously monitored through a system of vehicular review; in the Constitution of the Republic of Ecuador the right to live in a healthy environment free from pollution is recognized